Reducing the noise of pressure pulp screen - Oddo, R.; Nicolas, J.; Panneton, R. (Canadian Acoustics, 1994)
A pressure pulp screen is a device able of classifying and separate fibers in paper pulp. The machine is made of two concentric cylinders closed at both extremities. The inner cylinder, called `basket' is perforated. The size and the form of holes is determined by the considerations on the quality of paper and the time where classification occurs during the process. The pulp is injected under pressure in the centre part of the machine. The accepted pulp goes through the holes of the basket and is collected by a pipe connected at the part between the two cylinders. Refused pulp is collected by an other pipe in the centre part of the machine. In order to clean the holes of the basket, the depression made by blades moving at less than 5 mm of the inner side of the basket is used. These blades are supported by a rotor running at 1150 rpm. The noise of this machine is characterised by a discrete spectrum in middle and high frequencies. Levels depends of the consistency of pulp (1 to 4% of fibers), the type of holes (vertical slots, profiled circular holes) and speed of rotation of the rotor. Classical sound power levels in industry are 95 dB(A) for a basket with circular holes for a diameter of 90"